Conducta disruptiva y su influencia en el rendimiento escolar - Pérez Astudillo, Marjorie Elizabeth (2020)
This case study aims to identify disruptive behaviors, through psychotherapeutic techniques, to improve the school performance of a student of the "Adolfo María Astudillo" Educational Unit, in the city of Babahoyo. Disruptive behaviors are understood as those that have a negative influence on the teaching-learning process and cause a severe mismatch in school life. For data collection, the open and clinical interview, observation and psychometric tests were used. In the cognitive area, a negative belief towards his mother can be evidenced because he considers her a bad mother. In the cognitive area an automatic thought is evident: my mother is a bad mother loves my brother more than me. In the behavioral area clear disruptive behaviors are shown in the classroom, among the most serious are discuss with your teacher, challenge class rules, fight and annoy your classmates, aggressive tendencies, etc. And in the emotional area there is a lack of empathy with the relationship with his teacher and classmates, due to the lack of self-control when he gets angry. Therefore, a therapeutic plan based on cognitive behavioral therapy will be designed to address this problem.